PERBEDAAN PERSEPSI TENTANG PROFESI KEPERAWATAN PADA SISWA SMA KELAS XII DI KABUPATEN KEBUMEN - hendry tamara yudha; handoyo -; Arnika Dwi Asti (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2010)
Nursing is a profession that it has special characteristic and criteria , nurses have body of knowledge and health service in society. The profession of nursing has declared it’s self as an independent profession in National Nursing Workshop in 1983. The students of senior high school as row input of nursing education probably has particular perception about profession of nursing. In order to observe perception difference of boys and girls senior high school students in twelve grade towards profession of nursing. The research was a comparative study with a cross sectional approach. The research subjet were all senior high school students in twelve grade in Kebumen district, annual period of 2006/ 2007. Samples were taken by grade cluster sampling in 10 highschool. Insrument that adopted from the research formerly. The instrument was tested for it’s reliability and validity. Data collection on March 20 to April 20, 2007. Data analyzed used parametric t-Test Independent. It showed that (a) perception of boys senior high school students was good enough (75,94 %), good (20,3 %), and unsufficient (3,76 %) (b) perception of girls senior high school students was good enough (75,12 %), good (14,08 %) and unsufficient (10,8 %) (c) there was a perception difference between boys and girls senior high school students significantly. There were significant differences of student perception class XII between boys and girls at senior high school of Kebumen towards profession of nursing. Keywords : Perception, Senior high school students, Profession of nursing